Has There Been a She-covery? The Financial Crisis of 2008 and Its Impact on the Ontario Labour Market - Lewchuk, Wayne (Relations industrielles / Industrial Relations, 2013)
SummaryThe labour market turmoil associated with the financial crisis that began in late 2008 provides an opportunity to test the effect of the feminization of labour markets on how modern labour markets function in times of crisis (Armstrong, 1996; Vosko, 2000; Korkki, 2011). This paper will focus on two related questions. The first is whether men and women had different experiences as labour markets began to recover in November 2010. The second is whether the standard employment contract, that implies that workers with more seniority will be offered a degree of employment security in exchange for loyalty to a company, has frayed.These questions are explored by comparing the pre- and post-financial crisis labour market outcomes of 791 individuals employed in an area centred on Toronto and bounded by Hamilton in the west and Oshawa in the east. Evidence is presented on changes in having paid employment, the degree of employment security, the form of the employment relationship, and the characteristics of the employment relationship. Study participants completed a detailed survey describing their employment in June 2005 and again in November 2010. The paper assesses the accuracy of reports that suggest that the quality of employment had returned to pre-financial crisis levels by the spring of 2011 (Tal, 2011; Cross, 2011).The findings suggest there has been a gendered dimension to the post-financial crisis recovery in labour markets. However, the nature of this effect is not as simple as women finding more secure, better paying employment, or men being forced into less secure employment. For the sample as a whole, men were marginally more likely than women to be in paid employment. Young men were the most successful in finding more secure employment. Middle-aged men were the most likely to remain in paid employment in the post-financial crisis labour market, but at the cost of accepting less secure employment and employment that was less likely to have the characteristics of the standard employment relationship.